ARTIKEL TINJAUAN: METODE PENGAMBILAN SAMPEL DALAM VALIDASI PEMBERSIHAN - Een herliani; Patihul Husni (Farmaka, 2018)
Cleaning Validation is a critical point in the quality assurance of the pharmaceutical industry and must comply with  CPOB / cGMP. Cleaning Validation is a documented process that proves the effectiveness and consistency in cleaning pharmaceutical production equipment (Galatowitsch, 2000). Sampling method is swab method and and rinse method. Library search is done online using Google and Schoolar Google, using keywords related to cleaning validation. This review article contains information on cleaning validation and sampling methods used in cleaning validationKeywords: cleaning validation, swab method,  rinse method, CPOB